2016
DOI: 10.1016/j.jfma.2015.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol reverses morphine-induced neuroinflammation in morphine-tolerant rats by reversal HDAC1 expression

Abstract: Resveratrol restores the antinociceptive effect of morphine by reversing morphine infusion-induced spinal cord neuroinflammation and increase in TNFR1 expression. The reversal of the morphine-induced increase in TNFR1 expression by resveratrol is partially due to reversal of the morphine infusion-induced increase in HDAC1 expression. Resveratrol pretreatment can be used as an adjuvant in clinical pain management for patients who need long-term morphine treatment or with neuropathic pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…The effects of HDACi on morphine tolerance are controversial. Some studies have indicated that HDACi can enhance the analgesic effects of morphine and attenuate morphine tolerance ( Dobashi et al, 2010 ; Tsai et al, 2016 ; Hou et al, 2017 ; Liao et al, 2018 ). However, some studies have demonstrated that chronic morphine treatment with simultaneous SAHA treatment can enhance opioid-induced hyperalgesia ( Liang et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…The effects of HDACi on morphine tolerance are controversial. Some studies have indicated that HDACi can enhance the analgesic effects of morphine and attenuate morphine tolerance ( Dobashi et al, 2010 ; Tsai et al, 2016 ; Hou et al, 2017 ; Liao et al, 2018 ). However, some studies have demonstrated that chronic morphine treatment with simultaneous SAHA treatment can enhance opioid-induced hyperalgesia ( Liang et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Up-regulation of HDAC2 in neurons by HIV TAT was associated with down-regulation of CREB and CaMKIIa genes that are known to regulate neuronal activity, suggesting the possible role of HDAC in HIV-associated neurocognitive disorder (44). Previous studies by Tsai et al showed that morphine induced HDAC1 up-regulation in rat spinal cord dorsal horn, which contributed to neuro-inflammation and subsequent tolerance (45). Therefore, it will be interesting to investigate the detailed mechanisms by which HIV and opioids modulate HDAC activities, and future studies will also examine how abnormal HDAC activities regulate host response to opioids and HIV.…”
Section: Disscussionmentioning
confidence: 95%
“…In tactile allodynia caused by SNL, intrathecal injection of resveratrol can reduce the activity and expression of NOS, and alleviate tactile allodynia in rats with NPP (Pérez-Severiano et al, 2008). In a study by Tsai et al (2016), intrathecal injection of resveratrol reversed the increase in histone deacetylase 1 (HDAC1), TNF-α, and TNF receptor 1 (TNFR1) expression induced by long-term morphine infusion, and restored the antinociceptive effect in morphine-tolerant rats. Proanthocyanidins (PAs) are polyphenols in plant foods that have many health benefits, including cancer prevention, cardiovascular protection, and diabetes prevention (Zhang et al, 2016).…”
Section: Natural Medicines and Their Extractsmentioning
confidence: 99%
“…The use of microglial inhibitors can reverse the expression of pro-inflammatory factors during morphine infusion. The expression of microglial surface markers Iba-1, purinergic receptors (P2X4R and P2X7R), and TLR4 increases with increasing levels of glial medium (Tsai et al, 2016;Bisht et al, 2018). Targeting microglial activation may have great research value for the treatment of NPP and the prevention of morphine tolerance.…”
Section: Microglial Activation: a Bridge Between Npp And Morphine Tolmentioning
confidence: 99%